1997
DOI: 10.1136/adc.76.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of infant feeding and gluten intake on coeliac disease

Abstract: Objectives-To study the impact of infant feeding habits and actual gluten intake on gluten induced enteropathy. Methods-A case-referent design, controlling for the HLA alleles conferring increased genetic risk, was used. All 164 siblings of 97 probands were investigated. Eighty five of the siblings, carrying the genes DQA1*0501-DQB1*02 conferring susceptibility for the disease, were investigated by interview, food recording, and taking a small intestinal biopsy sample. Eight cases of silent coeliac disease wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
2
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 29 publications
(15 reference statements)
1
76
2
1
Order By: Relevance
“…The risk of a sibling to a CD patient to develop disease is about 20 to 60 times higher than that of the normal population (l s =20 ± 60). 2,3 Moreover, the twin concordance in CD is high. A recent large population based study in Italy using 59 twin couples, claims a proband-wise concordance of 85 ± 95% for monozygotic twins and about 25% for dizygotic twins (Romino et al, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of a sibling to a CD patient to develop disease is about 20 to 60 times higher than that of the normal population (l s =20 ± 60). 2,3 Moreover, the twin concordance in CD is high. A recent large population based study in Italy using 59 twin couples, claims a proband-wise concordance of 85 ± 95% for monozygotic twins and about 25% for dizygotic twins (Romino et al, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of data of four studies indicated that children being breast fed at the time of gluten introduction had a 52% reduction in risk of developing CD compared with their peers who were not breast feeding at the time of gluten introduction. With the exception of one small study, 6 all the studies included in the review also showed a statistically significant association between increasing duration of breast feeding and reduced risk of CD. The sample size of that study was, however, quite small (see table 1), and there was a risk of a type II error.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot tell, from the results of the primary studies, whether breast feeding provides a permanent protection against the development of CD or whether the practice only delays the onset of symptoms. All the included studies, except Ascher et al, 6 had used healthy children without symptoms of CD as controls without subjecting them to small intestinal biopsies. CD can be notoriously asymptomatic and the absence of symptoms does not necessarily mean absence of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations